Analysis of Joint Property Disputes Undergoing Mediation: A Case Study of the Pasir Pangaraian Religious Court - Yenrizka Gusmaria; Tri Setiady (al-Afkar, Journal For Islamic Studies, 2025)
Marriage is an inner relationship between a man and a woman whose aim is to form an eternal family based on the Almighty Godhead. Joint assets are assets that are acquired throughout the marriage from the time the marriage takes place until the marriage ends or the dissolution of the marriage due to divorce, death or a court decision. Mediation is an effort to resolve conflict by involving a neutral third party, who does not have the authority to make decisions that helps the disputing parties reach a resolution (solution) that is acceptable to both parties. This research aims to analyze joint assets from the perspective of statutory regulations, customary law and Islamic law, as well as dispute resolution through mediation. In this research, the author uses case study data from the Pasir Pengaraian religious court to find out the problems of joint property disputes which were resolved through mediation. The results of this research show that even though there are problems that arise because one party feels that the distribution is unfair, they can find a middle point through mediation. Therefore, mediation has become an important mechanism in law and mediation provides an effective solution to resolve disputes between the parties involved without having to go through formal justice channels. By holding mediation, the disputing parties hand over the resolution of their dispute to one or more independent arbitrators who are considered experts in the matter